Format-preserving encryption for DateTime - Zheli Liu; Chunfu Jia; Jingwei Li; Xiaochun Cheng (2010 IEEE International Conference on Intelligent Computing and Intelligent Systems, 2010)
In many applications, such as encryption of DateTime field in database, it is desirable to encrypt items from an arbitrarily sized set with the specified format described as "YYYY-MM-DD HH:MM:SS" onto that same set. Unfortunately, conventional block ciphers such as DES, 3DES or AES are unsuitable for this purpose. The solution to it belongs to the format-preserving encryption (FPE) category. In the paper, we present an FPE scheme for DateTime based on "rank-then-cipher" mode, and then analyze its security and efficiency. We further propose a new more efficient approach named "reference-based offset encryption" to resolve the FPE problem on DateTime domain, which can be applied in message space comprised of fixed-length strings taken over some alphabet as well.